(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Despite tourism destinations being recognized as ideal contexts for coopetition due to their structural interdependence and network characteristics, coopetition research in tourism remains severely underexplored, representing only 5.6% of total coopetition scholarship. This study provides a comprehensive scientometric analysis to map the intellectual structure, identify key contributors, and reveal emerging trends in this nascent field. Using Web of Science and Scopus data spanning 1996-2025, we analyzed 157 publications employing CiteSpace software to generate co-citation networks, keyword co-occurrence patterns, and cluster analysis. The analysis reveals significant geographic concentration, with 43.7% of research originating from European institutions and 28.5% from the Americas. Four distinct intellectual communities emerge: conceptualization and operationalization studies, trust and network governance mechanisms, strategic applications and performance outcomes, and entrepreneurial cognition. The field demonstrates evolution from basic definitions toward multidimensional constructs encompassing managerial, strategic, behavioral, and contextual dimensions, yet exhibits structural fragmentation with minimal international collaboration. Tourism research predominantly treats coopetition as an explanatory variable for strategic advantages rather than investigating its formation mechanisms, contrasting with broader coopetition literature. Critical gaps include absence of intra-organizational coopetition studies, limited cross-destination comparative research, and narrow focus on specific tourism types. This research advances tourism coopetition scholarship by documenting disciplinary knowledge flows through dual-map overlay analysis, quantifying structural fragmentation that impedes knowledge accumulation, and establishing temporal evolution patterns across consolidation and acceleration phases, thereby providing actionable priorities for destination managers and researchers seeking to bridge theoretical development with practical implementation.